Microencapsulation Delivery System in Food Industry—Challenge and the Way Forward. (13th July 2020) - Yang, Mingyi; Liang, Ze; Wang, Lei; Qi, Ming; Luo, Zisheng; Li, Li
Abstract : Microencapsulation is a promising technique, which provides core materials with protective barrier, good stability, controlled release, and targeting delivery. Compared with the pharmaceutical, cosmetic, and textile industries, food processing has higher requirements for safety and hygiene and calls for quality and nutrition maintenance. This paper reviews the widely used polymers as microcapsule wall materials and the application in different food products, including plant-derived food, animal-derived food, and additives. Also, common preparation technologies (emphasizing advantages and disadvantages), including spray-drying, emulsification, freeze-drying, coacervation, layer-by-layer, extrusion, supercritical, fluidized bed coating, electrospray, solvent evaporation, nanocapsule preparation, and their correlation with selected wall materials in recent 10 years are presented. Personalized design and cheap, efficient, and eco-friendly preparation of microcapsules are urgently required to meet the needs of different processing or storage environments. Moreover, this review may provide a reference for the microencapsulation research interests and development on future exploration.